Study the Influence of Sn Dopant on the Some Structural and Optical Properties of Pure Cadmium Oxide(CdO) Thin Films - Shehab, A. A.; Mahmoud, T. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research , pure Cadmium Oxide thin films were prepared by thermal evaporation Under vacuum method , where pure cadmium metal was deposited on glass Substrate in Room temperature (300K) at thickness (400 ± 30) nm with Deposition rate(1.1 ± 0.1) nm/sec And then we oxidize a pure cadmium Film in Temperature ( 350ºC ) for one hour with existence air flow. This research contained study of the influence of doping process by Tin metal (Sn) with two different ratios (1,3) % at substrate temperature (473K ) on the some structural properties of pure Cadmium oxide films . X-Ray diffraction pattern showed that all prepared films ( undoped and Sn doped ) are polycrystalline and of cubic kind with preferred orientation along [111] plane for all doped And undoped films , and the average grain size would Decrease with apparent shape when The ratio of Sn dopant increases until (43nm) at ratio (3%) , also this research included a study of the influence of Sn dopant with a mentioned ratios on the some optical properties of pure CdO films, such as calculation of the value of optical energy gap to allow direct transition, and studied and calculated the absorption coefficient . The optical investigation showed that all films prepared ( undoped and Sn doped) have Absorption coefficient with a value larger than (α >10 4 cm-1) and this value was increased when the increase of the ratios of Sn dopant specially in the low photon energy The optical energy gap was founded equal to (2.15 eV) for pure Cadmium Oxide film and it will decrease when the ratio of Sn dopant increases until (1.925 eV) For ratio (3%) .